The Moderating Effect of Decent Work on Employee Commitment and Organisational Citizenship Behaviour in the Construction Sector - Muchakubvura, Dzidzai; Chikove, Munyaradzi; Msosa, Steven Kayambazinthu (Dr. Viktor Koval, 2026)
Background. Turnover remains high in Zimbabwe’s construction sector, which employs thousands of skilled and unskilled workers and contributes significantly to the national economy. However, excessive staff turnover reduces productivity and revenues. The construction sector’s potential and dynamism are directly related to the level of employee commitment, organisational citizenship behaviour, and fair work experience of its employees. These are key elements of sustainable, long-term human resource management that can help construction companies address the diverse needs and expectations of both potential and existing employees while preserving long-term business opportunities. Purpose. This study aimed to examine the moderating effect of decent work on the relationship between employee commitment (EC) and organisational citizenship behaviour (OCB) in the Zimbabwean construction sector. Findings. The study adopted a quantitative methodology to obtain data from a convenience sample of 200 participants employed in the construction industry. The data were analysed using SmartPLS 4.0 and SPSS. The findings show a strong relationship among the variables, highlighting their significant roles in explaining the variance in the constructs. Specifically, the results show that Decent Work is positively related to Employee Commitment (β = 0.456, p < 0.001) and Organisational Citizenship Behaviour (β = 0.178, p < 0.025); Employee Commitment is positively associated with Organisational Citizenship Behaviour (β = 0.191, p < 0.019). Furthermore, the results show that Decent Work (DW) moderates the relationship between Employee Commitment (EC) and Organisational Citizenship Behaviour (β = 0.054, p < 0.043). Implications. This research provides information on the policy guidelines adopted by governments regarding the promotion of the concept ‘decent work’ in the construction sector. The findings suggest that construction firm managers should adopt decent work practices to retain top talent. Furthermore, employee engagement and corporate citizenship must be enhanced through initiatives that support employee well-being. This study provides governments with valuable information for developing policies that foster the creation of high-quality employment opportunities in the construction industry. Therefore, organisations seeking to develop employee engagement and corporate citizenship should consider creating a high-quality work environment.